2010
DOI: 10.1007/s11764-009-0110-5
|View full text |Cite|
|
Sign up to set email alerts
|

An update of controlled physical activity trials in cancer survivors: a systematic review and meta-analysis

Abstract: Current evidence suggests many health benefits from physical activity during and post cancer treatments. Additional studies are needed in cancer diagnoses other than breast and with a focus on survivors in greatest need of improvements for the health outcomes of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
926
6
39

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,128 publications
(1,021 citation statements)
references
References 112 publications
50
926
6
39
Order By: Relevance
“…These findings are also in line with Speck and colleagues [5] who, based on eight trials, concluded with small to moderate effect of physical exercise on muscle strength.…”
Section: Effects Of Physical Exercisesupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are also in line with Speck and colleagues [5] who, based on eight trials, concluded with small to moderate effect of physical exercise on muscle strength.…”
Section: Effects Of Physical Exercisesupporting
confidence: 91%
“…The findings are in line with a systematic review and a meta-analysis by Speck et al [5] based on five trials reporting muscle mass as outcome. This review concluded with small effects sizes in favour of different physical activity interventions compared with usual care in cancer survivors.…”
Section: Effects Of Physical Exercisesupporting
confidence: 90%
See 2 more Smart Citations
“…Participating specialist practitioners who were physiotherapists also suggested that the role of physical activity, especially in the management of fatigue and breathlessness, should be incorporated as a key component of RDSI rather than only appearing in the written information. Given the strong evidence base for structured activity in the management of cancer‐related symptoms (Schwartz, Mori, Gao, Nail, & King, 2001; Speck, Courneya, Mâsse, Duval, & Schmitz, 2010) this has been added as a key component to RDSI.…”
Section: Discussionmentioning
confidence: 99%